TINGKAT PARTISIPASI ANGGOTA KELOMPOK TANI DALAM PENYUSUNAN PROGRAMA PENYULUHAN DI DESA PURWAJAYA KECAMATAN LOA JANAN (The Participation Level of Farmers Group Members to Compile the Extension Programme in Purwajaya Village Loa Janan District) - DARYANA DARYANA; JURAEMI JURAEMI; NDAN IMANG (Universitas Mulawarman (University of Mulawarman), 2019)
The success of achieving extension program implementation can not be separated from the participation of farmers group members since its preparation. In connection with that, this research was conducted to know the participation level of farmers group members to compile the agriculture extension programme. The participation level of farmers group members to compile the agriculture extension programme was measured by low, middle, and high categories. This study was held from September to November 2017. Sampling method was stratified random sampling with a total of 36 respondents. The data collected in this research were pimary and secondary data. Data collection was done by observation and direct interviews with the respondents. Data analysis were done by using likert method. The result of research shows that respondents score average was 40.53 which meant the participation level of farmers group members to compile the extension programme is categorized high.